Analisis Kemampuan Pemecahan Masalah Matematis dan Self-efficacy Siswa Tingkat SMP pada Materi Kubus - Fera Agustin; Asep Sahrudin; Ika Yunitasari (Radian Journal: Research and Review in Mathematics Education, 2022)
This study aims to determine the mathematical problem solving ability and self-efficacy of students in solving problems on the cube material. The research was carried out using qualitative methods, the instruments used in this study were: (1) the problem-solving ability test instrument, the test questions consisted of 5 questions with cube material; (2) a self-efficacy questionnaire instrument with 17 statement items; and (3) interview instruments. Based on the results of data analysis obtained 2 students with high problem solving ability category, 2 students with middle problem solving ability category, and 2 students with low problem solving ability category. The results of the S1 self efficacy questionnaire research are in the high self efficacy category with a score of 64% , S2 is in the medium category with a score of 54%, S3 is in the high category with a score of 66%, S4 is in the medium category with a score of 42%, S5 is in the low category with a score of 40% and S6 is in the medium category with a score of 39%